Twitter Reactions on Coronavirus across UK - How British behaved differently to the pandemic across country? - Nasir, Sannia (2020)
COVID-19 has generated a plethora of discussions on social media. Twitter has been extensively used as a platform to discuss facts, share opinions, and express sentiments during the times of crisis. It is imperative to understand that the response to COVID-19 in different areas may be dependent upon local cases, government policies, health infrastructure and multiple socioeconomic factors. As the pandemic has affected everyone’s’ life on a different scale, it is essential to capture the public’s main topics of concern, and how people in different locations have reacted to the situation. In the event of crisis, monitoring people's responses across various events and topics will be extremely necessary for policy makers to be able to devise effective policies. In this dissertation, twitter data is used to perform region-specific exploratory analysis on people’s discussion and sentiments about COVID-19 in the UK. Topic modelling and sentiment analysis is used to unravel the intra-region dynamics. It shows that people across different regions discuss the same topics in different contexts. The study also discusses how sentiments of people change over time and are heavily influenced by government policies and information on media. Overall, the proposed framework shows the potential of using twitter analysis to assist the local authorities in designing policies for new interventions.